Summertime Soil-Atmosphere Ammonia Exchange in the Colorado Rocky Mountain Front Range Pine Forest - Amy Hrdina; Alexander Moravek; Heather Schwartz-Narbonne; Jennifer Murphy (Soil Systems, 2019)
Understanding the NH3 exchange between forest ecosystems and the atmosphere is important due to its role in the nitrogen cycle. However, NH3 exchange is dynamic and difficult to measure. The goal of this study was to characterize this exchange by measuring the atmosphere, soil, and vegetation. Compensation point modeling was used to evaluate the direction and magnitude of surface-atmosphere exchange. Measurements were performed at the Manitou Experimental Forest Observatory (MEFO) site in the Colorado Front Range by continuous online monitoring of gas and particle phase NH3-NH4+ with an ambient ion monitoring system coupled with ion chromatographs (AIM-IC), direct measurements of [NH4+] and pH in soil extracts to determine ground emission potential (Γg), and measurements of [NH4+]bulk in pine needles to derive leaf emission potential (Γst). Two different soil types were measured multiple times throughout the study, in which Γg ranged from 5 to 2122. Γst values ranged from 29 to 54. Inferred fluxes (Fg) from each soil type predicted intervals of emission and deposition. By accounting for the total [NH4+] pool in each compartment, the lifetime of NH3 with respect to the surface-atmosphere exchange in the soil is on the order of years compared to much faster naturally occurring processes, i.e., mineralization and nitrification.